Seroprevalence of Ehrlichia canis infection among privately-owned dogs in northern Bulgaria - TSACHEV, I.; PAPADOGIANNAKIS (E.I. ΠΑΠΑΔΟΠΑΝΝΑΚΗΣ) E. I.; KONTOS (Β. ΚΟΝΤΟΣ) V.; ZARKOV, I.; PETROV, V.; PELAGIC, V. (Journal of the Hellenic Veterinary Medical Society, 2017)
A serologic survey was carried out to detect the prevalence of Ehrlichia canis antibodies among privately-owned dogs in the counties of Varna, Silistra, Ruse, Montana, Veliko Tarnovo and Pleven of northern Bulgaria. A total of 120 serum samples were IFA tested for anti-Ehrlichia canis IgG antibodies. A mean seroprevalence rate of 37.5% was recorded with Varna county showing the highest value (60%) followed by Silistra (55%), Ruse (30%), Montana (30%), Veliko Tarnovo (25%) and Pleven (25%) counties. These results clearly show that dogs residing in northern Bulgaria are highly exposed to E. canis.